2017
DOI: 10.1016/j.triboint.2016.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Normal and tangential oil film stiffness of modified spur gear with non-Newtonian elastohydrodynamic lubrication

Abstract: A new normal stiffness model of the oil film is established by the viscous-elastic fluid between a spur gear drive being equivalent to a massless spring element, and the tangential stiffness model is proposed according to the hypothesis of equal shear stress on laminar element surfaces. Effects of operating parameters (contact force and rotation speed) and geometry parameters (module, tooth number,pressure angle and modification) on the oil film stiffness from the root to the tip are investigated. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 27 publications
(33 reference statements)
2
29
2
Order By: Relevance
“…In EHL contact, the stiffness of oil film between mating gear pair is defined as 16 where k f is the oil film stiffness and B is the face width equal to the length of the contact line of two meshing gear teeth that is perpendicular to the x direction. 1,13 Δ is the increment symbol.…”
Section: Tribological and Thermal Propertiesmentioning
confidence: 99%
“…In EHL contact, the stiffness of oil film between mating gear pair is defined as 16 where k f is the oil film stiffness and B is the face width equal to the length of the contact line of two meshing gear teeth that is perpendicular to the x direction. 1,13 Δ is the increment symbol.…”
Section: Tribological and Thermal Propertiesmentioning
confidence: 99%
“…Add formula (9) and formula (10) to (1) and to (4), and the dimensionless elastohydrodynamic lubrication control equation can be obtained.…”
Section: Nondimensionalize Equationsmentioning
confidence: 99%
“…The impacts of the input torque, surface roughness, and lubricant temperature on the gear contact fatigue under tribodynamic condition were also investigated. Zhou et al established a new normal stiffness model of oil film by viscous-elastic fluid between a spur gear drive equivalent and a massless spring element and proposed a tangential stiffness model according to the hypothesis of equal shear stress on laminar element surfaces [4]. It indicated that the rational parameter match is valid in mesh impact reduction and stationarity enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the use of non-standard pinion and gear of unequal tooth thickness could aid in reducing the wear damage. Zhou et al [29] investigated the normal and tangential oil film stiffness of modified spur gears with non-Newtonian elastohydrodynamic lubrication. They revealed that the modification was valid for inhibiting the jump of oil film stiffness and improving the gear wear resistance.…”
Section: Introductionmentioning
confidence: 99%